PENGARUH TAKARAN PUPUK ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) - Rahma, Meci Yuniastuti (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2018)
The research objective was to study the effect of organic and inorganic fertilizer on the growth and production of lettuce. This research was conducted from February 2017 to April 2017 at Green House, Faculty of Agricultural,Sjakhyakirti University Palembang. The research used Randomized Block Design (RAK) with 12 treatments and repeated 3 times. The treatment in this research was K (50 g.crop-1 cowmanure and 0 g.crop-1NPK fertilizer), L (50 g.crop-1 cow manure and 1 g.crop-1 NPK fertilizer ), M (50 g.crop-1 cow manure and 2 g.crop-1 NPK fertilizer), N (50 g.crop-1 cow manure and 3 g.crop-1NPK fertilizer), O ( 80 g.crop-1 cow manure and 0 g.crop-1 NPKfertilizer), P (80 g.crop-1 cow manure and 1 g.crop-1 NPK fertilizer), Q (80 g.crop-1 cow manure and 2 g.crop-1NPK fertilizer), R (80 g.crop-1 cow manure and 3 g.crop-1NPK fertilizer), S (110 g.crop-1 cow manure and 0 g.crop-1 NPK fertilizer), T (110 g.crop-1 cow manure and 1 g.crop-1NPK fertilizer), U (110 g.crop-1 cow manure and 2 g.crop-1 NPK fertilizer), V (110 g.crop-1 cow manure and 3 g.crop-1 NPK fertilizer). The variables observed in this study were plant height (cm), number of leaves (strands), number of roots, wet weight of plant (g), dry weight of plant (g). The results showed that the organic fertilizer of cow manure and inorganic NPK fertilizer have no significant effect on the growth but has a significant effect on the production of lettuce plant. However, the U (110 g.crop-1 cow manure and 3 g.crop-1 NPK fertilizer) showed the best production of many leaves and wet trimming weight of lettuce.